If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1(6x + 6) = 2x + -38 Reorder the terms: 7x + -1(6 + 6x) = 2x + -38 7x + (6 * -1 + 6x * -1) = 2x + -38 7x + (-6 + -6x) = 2x + -38 Reorder the terms: -6 + 7x + -6x = 2x + -38 Combine like terms: 7x + -6x = 1x -6 + 1x = 2x + -38 Reorder the terms: -6 + 1x = -38 + 2x Solving -6 + 1x = -38 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -6 + 1x + -2x = -38 + 2x + -2x Combine like terms: 1x + -2x = -1x -6 + -1x = -38 + 2x + -2x Combine like terms: 2x + -2x = 0 -6 + -1x = -38 + 0 -6 + -1x = -38 Add '6' to each side of the equation. -6 + 6 + -1x = -38 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = -38 + 6 -1x = -38 + 6 Combine like terms: -38 + 6 = -32 -1x = -32 Divide each side by '-1'. x = 32 Simplifying x = 32
| -11=0-5/6 | | 45x+26x+110=0 | | y=5x-21 | | W^2=w+1 | | 5-3(4+6)= | | 4x-2=5(x+10) | | 2-0x=-8 | | 9-2(x+3)+6x= | | e^5x+6=.46 | | 5x+12+4y=32 | | 8-2x=-26 | | -15+x=-8 | | 4+5n=8n+7 | | 5/6x(x-3)-10(x-3) | | 3x/-0.5=1.9 | | F(x)=x^3-x+1 | | 48m^2-3x^2=0 | | n/2-4 | | 3(4z-1)-2(z+1)=3(z+1) | | -4(8v-1)=32-4v | | 5(x+2)=4(x-2)+x | | -2r-5=2r+4 | | 5(x+4)-(4x-7)=4 | | x+2x+5=26 | | -7(6a-6)-3a=222 | | -2y+2(-6-4)=9+2(1-y) | | 2=(10=z)/-3 | | 1000c^3+27=0 | | y=X^3+3X^2-45X | | 2(x-6)-(5x+3)=4(6x+3) | | x+2x+5=27 | | 125a^3-8b^3=0 |